Recommendation content matters! Exploring the impact of the recommendation content on consumer decisions from the means-end chain perspective. (February 2023) - Yang, Tiantian; Yang, Feng; Men, Jinqi
Abstract: Consumers increasingly rely on social media to obtain product information. The vlog, a new kind of social medium, has been adopted by sellers to connect with consumers. Through this platform, sellers can cooperate with vloggers to recommend products or services to consumers. Extending beyond the previous perspective that consumers' perceptions and behaviors are influenced by vloggers' attributes, we herein investigate the influence of recommendation content. Drawing on the means-end chain framework, this paper investigates how the attributes of recommendation content affect consumers' intention to adopt (i.e., follow) the recommendation. Data collected from 513 respondents provides support for the proposed influences. The results indicate that source credibility, content diagnosticity, and content serendipity drive consumers' recommendation adoption intention. This research contributes to the literature on rec-vlog marketing by clarifying the significant role of recommendation content. Implications are discussed regarding these findings. Highlights: Helpful recommendation content (RC) is more likely to be adopted by consumers. Source credibility, content diagnosticity, and content serendipity are attributes of helpful RC. Helpful RC improves consumers' perception of satisfaction with the recommendation. Means-end chain framework helps to explain the formation mechanism of consumer adoption.